Effect of annealing on the tribological behavior of Zr-based bulk metallic glass - Hsu-Ming Lien; Nicolás Molina; Aisha Lizaola; Michael Chandross; Filippo Mangolini (APL Materials)
Bulk Metallic Glasses (BMGs) are promising materials for several applications owing to their high elastic limit and resistance to permanent deformation. However, BMGs have lower wear resistance than their crystalline counterparts during dry sliding. The formation of a composite material with crystalline phases dispersed in the BMG matrix through devitrification and partial crystallization at elevated temperatures has recently been proposed as an effective way to improve the wear resistance. However, our understanding of the origin of the improved wear behavior of annealed BMGs is still elusive. Here, a systematic evaluation of the effect of annealing temperature (from temperatures lower than the BMG glass transition temperature to temperatures higher than the BMG recrystallization temperature) on the friction and wear response of a Zr-based BMG, namely Vit105 (Zr52.5Cu17.9Ni14.6Al10Ti5), was performed. The results indicate that annealing Vit105 improves its wear resistance while also reducing the steady-state friction response when the annealing temperature is close to the glass transition temperature. Notably, the formation of a transfer film on the sapphire countersurface is highly dependent on the applied normal load and sliding time. Finally, the wear mechanism was found to be strongly dependent on the annealing temperature as a transition from a predominantly adhesive wear mechanism to an abrasive-dominated one was observed as the annealing temperature crossed the glass transition temperature. Altogether, the results of this work aid to our understanding of the tribological behavior of Zr-based BMGs in general, while also providing clues to strategies for the effective use of BMGs in tribological applications.